A project portfolio selection framework for transforming Iranian universities into entrepreneurial institutions - Nima Golghamat Raad; Mohsen Akbarpour Shirazi (Journal of Industry-University Collaboration (JIUC), 2020)
Purpose This research proposes a framework by which universities can define and implement projects that transform them into entrepreneurial universities. The framework helps decision-makers identify suitable goals and strategies, gather a list of projects to fulfill the goals and strategies and prioritize the projects and form a portfolio. Design/methodology/approach In the proposed framework, importance-performance matrix, hierarchical strategic planning, Delphi technique, DEMATEL-based ANP and a multi-objective model are used. The mathematical model consists of four objective functions including efficiency, quality and balance maximization and also cost and risk minimization. The proposed framework is applied to Amirkabir University of Technology, Tehran, Iran, and the results are brought in this paper. Findings The output of the proposed framework is a portfolio of projects that aims to transform a traditional university into a third-generation one. Although the final portfolio must be customized for different universities, the proposed steps of the framework can be helpful for almost all cases. Originality/value The suggested framework is unique and uses both qualitative and quantitative techniques for project portfolio selection.
Keywords: 330; DEMATEL-based ANP; Entrepreneurial university; Linear programming; Project portfolio selection; Strategic management